Chemical data of soil density fractions from Gaburumata mangrove, Ishigaki Island, Japan - Morimaru Kida (PANGAEA, 2025)
The study area, located along the Gaburumata River on Ishigaki Island, Okinawa Prefecture, Japan (24°30 extquotesingle18.5N, 124°14 extquotesingle52.2E), comprises a mangrove forest covering approximately 1.5 ha around the river estuary. The vegetation is dominated by Bruguiera gymnorrhiza. Transects were established at three points (upstream, midstream, downstream) running from north to south. Sampling was conducted in June 2022 at five depths: 0-10, 10-20, 20-40, 40-70, and 70-100 cm, respectively, using a stainless-steel soil auger. Samples were collected at ten locations along each transect at approximately equal intervals. Corresponding depth sections were composited to create one composite sample per depth per transect, which was then stored in plastic bags under cool, dark conditions and transported to the laboratory. Composited samples were frozen and subjected to vacuum freeze-drying for seven days. Subsequently, the freeze-dried soil was gently sieved through a 2 mm mesh sieve. Density fractionation was performed using an aqueous solution of sodium polytungstate (SPT-0, TC-Tungsten Compounds, Germany; SPT) with a density of 1.6 g cm^3 with the optimized protocol described in the accompanying paper. After density fractionation, each density fraction was freeze-dried, ground to powder, and measured for elemental analysis, stable carbon and radiocarbon analysis, and extractable metals analysis (Al, Fe, Ca, Mg).